2018
DOI: 10.1017/s1047951117002839
|View full text |Cite|
|
Sign up to set email alerts
|

Radiation exposure in transcatheter patent ductus arteriosus closure: time to tune?

Abstract: Lower doses of radiation can be achieved with subsequent recommendations: technical improvement, frame rate reduction, avoidance of biplane cineangiograms, use of stored fluoroscopy as much as possible, and limitation of fluoroscopic time. A greater use of echocardiography might even lessen the exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These values are less than prior studies of transcatheter PDA closure in infants with ELBW, 9 where reported mean radiation was 1278.9 mGy.cm, 2 , 29 and studies of a similar procedure in children ranging in age from 0 to 17.6 years of age, where reported mean radiation dose area product in that population was 1010 mGy.cm. 2 , 30 This reduction in radiation exposure is likely the result of several mitigation strategies used in our catheterization laboratory including the use of lower frame rates (7.5 frames/s) and collimation. In addition, our median fluoroscopy time of 4.5 minutes is shorter than comparable studies where reported mean fluoroscopy exposure duration was ranged from 4.99 to 12.9 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…These values are less than prior studies of transcatheter PDA closure in infants with ELBW, 9 where reported mean radiation was 1278.9 mGy.cm, 2 , 29 and studies of a similar procedure in children ranging in age from 0 to 17.6 years of age, where reported mean radiation dose area product in that population was 1010 mGy.cm. 2 , 30 This reduction in radiation exposure is likely the result of several mitigation strategies used in our catheterization laboratory including the use of lower frame rates (7.5 frames/s) and collimation. In addition, our median fluoroscopy time of 4.5 minutes is shorter than comparable studies where reported mean fluoroscopy exposure duration was ranged from 4.99 to 12.9 minutes.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Fluoroscopy times are still an issue in interventional procedures. 24 25 26 Mean fluoroscopy in most of the index procedures were below average as well as the in-hospital mortality rates. This may be evidence for an increasing number of complex interventions underrepresented in the interventional index procedures.…”
Section: Discussionmentioning
confidence: 96%
“…The frequent use of fluoroscopy may cause long-term side effects, depending on the dosage and duration of radiation exposure. In addition, the complexity of a procedure also adds to the duration of exposure, as in transcatheter PDA closure ( 15 ). Prolonged radiation not only harms pediatric patients who are more sensitive to radiation than adults ( 5 ), but it is also a risk to interventionists, especially those who routinely perform these procedures.…”
Section: Discussionmentioning
confidence: 99%